Test of Some Concentration of Piper aduncum L. Leaf Powder Extract to Control Setora nitens Wlk (Lepidoptera; Limacodidae) in Palm Oil Plant (Elaeis guineensis Jacq) - Muhammad Abdul Gani; Rusli Rustam; Desita Salbiah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Palm oil plant is one of plantation crop that grown by people of Indonesia, especially Sumatra (Riau). Setora nitens is one of the major pests in palm oil plantations. Management control to decrease the Setora nitens by using synthetic insecticides. Reducing the effects caused by synthetic insecticides, therefore need alternative in pest control techniques such as use organic insecticide derived from Piper aduncum L. The purpose of this research is to get Piper aduncum L. leaf powder extract concentrate that effective to control Setora nitens at palm oil plantations. This research was carried out experimentally by using Completely Randomized Design consisting of 5 treatments with 4 replications. The treatment consisting five level: SRH 0 (no concentration), SRH 1 (concentration of 25 g/liter of water), SRH 2 (concentration of 50 g/liter of water), SRH 3 (concentration of 75 g/liter of water) and SRH 4 (concentration 100 g/liter of water). Results showed that the concentration of 100 g/liter was able to kill Setora nitens by 45% and this has not been effective in controlling caterpillars Setora nitens because not reach 80%. The best concentration to kill 95% of the population of Setora nitens is 206% or 2.06 kg/l of water. Piper aduncum L. leaf powder extract has not been effective in controlling caterpillars Setora nitens at palm oil plantations. Keyword: Palm oil plant (Elaeis guineensis Jacq), Setora nitens, Piper aduncum L.